Optimizing Digital Marketing Efforts Through Neuromarketing: Systematic Review - Kemora, Haura; Pasaribu, Popy; Marlina, Asti; Himawan, Erry Nugroho (Moneter: Jurnal Keuangan dan Perbankan, 2024)
Neuromarketing, as a neuroscientific approach to understanding human behavior and decision-making in marketing, holds significant promise for optimizing digital marketing strategies. This systematic review addresses the gap in research regarding the impact of neuromarketing on digital platforms like social media, websites, and e-commerce. By synthesizing existing literature, the review aims to bridge consumer behavior analysis with neuromarketing applications in digital marketing. Key themes identified include a deeper understanding of consumer behavior, improved targeting and personalization, optimized user experience (UX), enhanced ad effectiveness, and data-driven decision-making. These themes highlight the practical benefits of integrating neuromarketing insights into digital marketing strategies, allowing businesses to connect with their target audience more effectively. Compared to traditional methodologies, neuromarketing techniques offer a more accurate understanding of consumer responses and preferences, facilitated by advanced neuroscience tools like EEG, fMRI, eye tracking, and facial coding. Leveraging these tools enables marketers to align digital efforts with consumer preferences, leading to a more efficient and cost-effective marketing approach.